2017
DOI: 10.1371/journal.pone.0179101
|View full text |Cite
|
Sign up to set email alerts
|

‘The Devil has entered you’: A qualitative study of Men Who Have Sex With Men (MSM) and the stigma and discrimination they experience from healthcare professionals and the general community in Bosnia and Herzegovina

Abstract: Men who have sex with men (MSM) are often exposed to unequal treatment in societies worldwide as well as to various forms of stigma and discrimination in healthcare services. Bosnia and Herzegovina (B&H) is a postconflict developing country located in Southeast Europe and the Western Balkans, where little is known about the experiences of MSM regarding their communities and interactions with healthcare services. The aim of this study was to explore the types of experiences MSM face and to assess the level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In our study, most health providers accepted that they did not have the requisite skills necessary to provide HIV services to MSM and FSWs (but most especially skills to handle MSM) and most of them felt that they needed to be trained in how to handle MSM, including how to effectively communicate with them. As has been documented elsewhere, lack of cultural and clinical competent by health providers can affect MSM and FSWs utilization of HIV and other health services [19, 33]. Although some of the health providers did not feel the need to be trained in how to handle MSM issues, evidence from prior studies suggest that health providers who have received sensitivity training [27, 28, 34] express greater acknowledgement of MSM patients in their clinics, endorse the need to treat MSM patients with high professional standards and demonstrate sophisticated awareness of the social and behavioral risks for HIV among MSM than those who have never attended such trainings.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, most health providers accepted that they did not have the requisite skills necessary to provide HIV services to MSM and FSWs (but most especially skills to handle MSM) and most of them felt that they needed to be trained in how to handle MSM, including how to effectively communicate with them. As has been documented elsewhere, lack of cultural and clinical competent by health providers can affect MSM and FSWs utilization of HIV and other health services [19, 33]. Although some of the health providers did not feel the need to be trained in how to handle MSM issues, evidence from prior studies suggest that health providers who have received sensitivity training [27, 28, 34] express greater acknowledgement of MSM patients in their clinics, endorse the need to treat MSM patients with high professional standards and demonstrate sophisticated awareness of the social and behavioral risks for HIV among MSM than those who have never attended such trainings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rates of men who disclosed their same-sex behaviors to healthcare professionals remain low in many places, ranging from 16% to 90% with a median of 61% [50,52]. Disclosing samesex behavior to healthcare professionals potentially influences men's health [53], but some studies also reported MSM being discriminated by health professionals when disclosing their same-sex behaviors [54,55]. A large proportion of MSM reported discomfort in discussing their same-sex behavior with healthcare professionals [52,56].…”
Section: Discussionmentioning
confidence: 99%
“…Although members of KP sub-groups may have different patterns of behaviour and social mixing that influence their HIV/STI risks, their vulnerabilities are augmented by common factors (Table 1). Often, KP experience structural barriers and societal discrimination that may increase their HIV/STI vulnerability by encumbering their access to healthcare [12][13][14][15][16][17]. Moreover, structural factors may not only directly affect susceptibility (e.g.…”
mentioning
confidence: 99%